In the realm of necessity (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
Gian Carlo Caselli’s contribution reflects on the debate regarding Article 41 bis – recently fueled by the hunger strike carried out by the anarchist Alfredo Cospito as a form of protest – re-examining its genesis and analyzing, also through a historical reconstruction, the effects produced by its application. Starting from these premises and reflecting on the current situation, the strategic importance of 41 bis as a fundamental tool in the fight against the Mafia is thus reaffirmed.
Keywords: Art. 41 bis; mafia crime; prison regime; pentitismo; fight against mafia